Role of magnetic resonance imaging as a diagnostic tool in evaluation of painful hip joint, and early detection of pathological changes, helpful to prognosticate and influence therapeutic decisions - Bollipo, Johny Prasad; Rao, Pasupuleti Bhimeswara (International Journal of Advances in Medicine, 2018)
Background: Magnetic Resonance Imaging (MRI) is a well-established imaging technique, which are available at most larger hospitals today. Due to the combination of this high contrast and the fact that it is a non-ionizing radiation, MRI is often used for investigation of a large range of pathologies in almost all parts of the body. This study was performed to describe the MRI features in various types of lesions causing painful hip joint, as well as identify the common lesions seen in painful hip joint and to analyse the severity and extent of the underlying lesion in various conditions of hip joint pain, and early detection of pathological changes helpful to prognosticate and influence therapeutic decisions. Methods: This descriptive study was done on 50 patients with complaints of hip joint pain were included into the study. Appropriate MRI sequences and multi-planar imaging performed for every patient. Results: Out of the 50 patients included in the study, 74% of them were males who were predominantly affected with hip pain. The most common age group which was affected was 51-60 years (20%) and 21-30 years (20%). The most common pathology amongst the patients was Avascular necrosis of femoral head seen in 44% of the patients, osteoarthritis was seen in 54 patients, Tuberculosis in 5 patients, 2 had Perthe’s disease, joint effusion was observed in 6 patients. Conclusions: MRI of the hip joint is an informative, diagnostic, non-invasive, rapid and accurate imaging modality for the assessment of hip pain and sufficient imaging modality for delineation of different hip joint pathology.